Effects of brain-computer interface-based rehabilitation on upper limb function, activities of daily living, and adverse events in patients with early stroke: a systematic review and meta-analysis. - Wei, Jing-Xue; Zhang, Yue-Mi; Liang, Shan-Shan; Li, Qi-Fu; Huang, Lang; Dai, Yuan-Hong; Bi, Zi-Ting; Xiao, Jing-Hua; Xu, Jian-Wen; Zhang, Yun-Shan (Frontiers in Aging Neuroscience, 2026)
Background: Brain-computer interface-based rehabilitation represents an emerging neurorehabilitation approach for post-stroke motor recovery, yet its comprehensive effects on patients in the early phase after stroke, typically defined as within 3 months of onset, remain to be fully established. This systematic review and meta-analysis evaluated effects of this intervention on upper limb function, activities of daily living, and adverse events in individuals with early stroke. Methods: This study was conducted following PRISMA guidelines. Eligibility criteria were established for randomized controlled trials that encompassed: (1) participants were adults (≥18 years) within 3 months of stroke onset with upper limb motor impairment; (2) interventions included brain-computer interface-based rehabilitation, and (3) outcomes that measured upper limb function, activities of daily living, and adverse events. A systematic search was performed across PubMed, Embase, Cumulative Index to Nursing and Allied Health Literature, Cochrane Library, and China National Knowledge Infrastructure databases from their inception to August 23, 2025. Two independent reviewers assessed eligibility, compiled data, and appraised methodological rigor, potential bias, and reliability of the evidence. Meta-analysis was performed using RevMan 5.4 (Cochrane Collaboration, UK) and Stata 18 (StataCorp., USA), applying random-effects models to calculate mean differences (MD) or risk ratios (RR) with 95% confidence intervals (CI). Subgroup analyses, meta-regression, sensitivity analyses, and publication bias assessments were conducted where appropriate. Results: Nine studies involving 642 participants (212 females and 430 males) with a mean age of 59.77 years were included. For primary outcomes, brain-computer interface-based rehabilitation significantly improved upper limb function in patients with early stroke (MD = 5.02, 95% CI: 3.20, 6.84). Subgroup analyses revealed that no statistically significant differences were observed in the improvement of upper limb functionality among various patient demographics and intervention characteristics (all p > 0.05). For secondary outcomes, the pooled analysis suggested a potential improvement in activities of daily living with BCI-based rehabilitation (MD = 7.68, 95% CI: 0.32, 15.03), although this finding was accompanied by very high heterogeneity (I 2 = 88%) and was not robust in sensitivity analyses, indicating low certainty of evidence. Subgroup analyses indicated that greater benefits might be observed in patients within 30 days after stroke onset and with intervention durations not exceeding 3 weeks. Regarding safety, preliminary data from a single study suggested no significant difference in adverse events between groups (p = 0.87), but the evidence base is currently insufficient to draw firm conclusions. Conclusions: Brain-computer interface-based rehabilitation is effective in improving upper limb motor function in patients with early stroke. Current evidence suggests a potential benefit for activities of daily living, but the evidence is of low certainty due to substantial heterogeneity and limited robustness. Subgroup analyses identified time from onset and intervention duration as potential effect modifiers for activities of daily living. Preliminary safety data from a single study are encouraging but insufficient to establish a safety profile. Further well-designed randomized controlled trials are needed to establish optimal brain-computer interface-based rehabilitation protocols, to confirm the potential benefit on activities of daily living with more robust evidence, and to evaluate long-term efficacy and safety. Systematic Review Registration: PROSPERO [Register number: CRD420251144151].